Field water management and irrigation practices in rice production in West Africa - Oke, Adebayo; Atengdem, P. B.; Zemadim, Birhanu; Cofie, Olufunke O. (International Water Management Institute, 2025)
Irrigated water management for rice involves optimizing water application to maximize yield while minimizing water use and environmental impact. Effective management includes controlling water flow into fields, ensuring adequate but not excessive flooding, and managing drainage to prevent waterlogging. Water quality is crucial, as salinity, sodium levels, and the presence of specific ions can negatively affect rice growth and productivity. By monitoring water quality parameters and adjusting irrigation practices, farmers can ensure optimal conditions for rice cultivation, promoting healthy growth and maximizing yields. This fact sheet provides more information on field water management in lowland rice production in West Africa.